2017
DOI: 10.1016/j.pocean.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The diel vertical migration patterns and individual swimming behavior of overwintering sprat Sprattus sprattus

Abstract: We addressed the behavioral patterns and DVM dynamics of sprat overwintering in a 150 m Norwegian fjord with increasing hypoxia by depth. An upward-facing echosounder deployed at the bottom and cabled to shore provided 4 months of continuous acoustic data. This enabled detailed studies of individual behavior, specifically allowing assessment of individual vertical migrations at dusk and dawn in relation to light, analysis of so-called rise-and-sink swimming, and investigation of the sprat' swimming activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…Schooling behaviours can also be adopted in complement to DVM, and often depend on the period of the day. Fish tend to disaggregate at night [58,59], sometimes in concert with an upward migration [59]. However, schooling is not always an appropriate strategy, as it can also attract predators and increase predation pressure [60].…”
Section: (Iv) Alternative Defence Mechanisms For Pelagic Organismsmentioning
confidence: 99%
“…Schooling behaviours can also be adopted in complement to DVM, and often depend on the period of the day. Fish tend to disaggregate at night [58,59], sometimes in concert with an upward migration [59]. However, schooling is not always an appropriate strategy, as it can also attract predators and increase predation pressure [60].…”
Section: (Iv) Alternative Defence Mechanisms For Pelagic Organismsmentioning
confidence: 99%
“…The primary motive for this daily commute to depth is visual predation, with primary consumers seeking refuge at depth during daylight hours and returning to the surface at night to feed (Bollens & Frost, 1991;Lampert, 1989;Ohman, 1990). Migratory amplitudes of DVM vary from a few tens or hundreds of metres for "jellyfish" (Haraldsson, Båmstedt, Tiselius, Titelman, & Aksnes, 2014;Kaartvedt, Klevjer, Torgersen, Sørnes, & Røstad, 2007) to mesopelagic depths (200-1,000 m) in the case of many salps, squid and fish (Gilly et al, 2006;Houssard et al, 2017;Solberg & Kaartvedt, 2017;Watanabe, Kubodera, Moku, & Kawaguchi, 2006;Wiebe, Madin, Haury, Harbison, & Philbin, 1979). Collectively, marine DVM is by far the largest coordinated movement of biomass on the planet-a continuous standing wave of pursued and pursuing animals extending across all but the highest latitude oceans (Wallace, Cottier, Brierley, & Tarling, 2013).…”
Section: Diurnal Vertical Migration and The Biological Pumpmentioning
confidence: 99%
“…Diel vertical migrations of sprat schools has been observed in fjords (Knudsen, Hawkins, McAllen, & Sand, ) and the Baltic Sea (Nilsson, ), and here in an open marine coastal system of the Holyhead Deep. Due to the mixed water column in the Holyhead Deep, the ‘antipredation window’ (Clark & Levy, ) determined by the depth variation in light irradiance would appear a key driver of these vertical migrations, as opposed to temperature or dissolved oxygen levels influencing migratory behaviour in more sheltered and stratified systems (Solberg & Kaartvedt, ). This study has shown that the magnitude of fish school DVM can change in correlation with the spring‐neap tidal cycle, due to its influence on irradiance depth in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Despite most of the Irish Sea being tidally mixed year round, resulting in homogenous vertical distributions of phytoplankton, some groups of zooplankton undertake diel vertical migrations (DVM; Irigoien, Conway, & Harris, ; Scrope‐Howe & Jones, ). Pelagic fish such as European sprat Sprattus sprattus , a zooplanktivorous forage fish, change their schooling behaviour and vertical distribution during the day, schooling deep during daylight, adopting shallower depth distributions after dawn and before dusk as they vertically migrate, and during darkness schools disperse (Nilsson, ; Solberg & Kaartvedt, ). In most species DVM is driven by light levels in the water column, Zooplanktivores need enough light to forage and maintain schools, but minimize predation risk by staying in as dark and deep water as possible (Bianchi & Mislan, ; Nilsson, ; Robison, ).…”
Section: Introductionmentioning
confidence: 99%